Pengaruh Husnuzzhan Terhadap Perilaku Prososial Pada Mahasiswa UIN Antasari Banjarmasin - Kiftiah, Mariatul; Mubarak, Mubarak; Hairina, Yulia (Jurnal Al-Husna, 2021)
This study aims to determine the effect of husnuzzhan on prosocial behavior in students of UIN Antasari Banjarmasin. This type of research is field research with a quantitative approach. The population in this study were active students of UIN Antasari Banjarmasin class 2018 and 2019. The sampling technique uesd was purposive sampling. The sample of this study amounted to 98 people. Based on the research conducted, the results obtained: 1) The level of husnuzzhan in the high category was 18 people (18,4%), while 68 people (69,4%) and low 12 people (12,2%). 2) The level of prosocial behavior in the high category was 11 people (11,2%), while 73 people (75,5%) and low 14 people (14,3%). 3) There is a husnuzzhan influence on prosocial behavior in UIN Antasari Banjarmasin students with a significance value of 0,000 (sig <  0,05) and a effective contribution of 21,9%.